Association of nutritional intake with myopia and astigmatism - Keyu Chen; Lianhong Pi; Haibo Xiong (Scientific Reports)
Abstract This study investigates the association between dietary lutein and zeaxanthin intake and the prevalence of myopia and astigmatism using data from the NHANES 2007–2008 survey. A total of 3,759 participants aged 12–59 years were analyzed. Myopia was classified into emmetropia, low myopia, and high myopia based on spherical equivalent refraction (SER), while astigmatism was categorized into high, low, and moderate based on right eye cylinder degree. Nutrient intake data, including lutein and zeaxanthin, were analyzed alongside sociodemographic and eye refractive data. Statistical comparisons between groups were conducted using t-tests and chi-square tests. Among participants, 58.7% were emmetropia group, 34.0% had low myopia, and 7.4% had high myopia. For astigmatism, 5.9% had high, 82.2% had low, and 12.9% had moderate levels. Significant differences were observed in sociodemographic factors, refractive measurements, and keratometry parameters across myopia and astigmatism groups (P < 0.05). However, dietary lutein and zeaxanthin intake showed no significant differences among these groups (P > 0.05). This cross-sectional study found no significant association between lutein and zeaxanthin intake and the prevalence of myopia or astigmatism.